A review and checklist of Panthea Hübner (Lepidoptera: Noctuidae: Pantheinae) with description of a new species from China - Hu, Gui-Lin; Shen, Qian-Ru; Santa-Rita, Jose Vicente Pérez; Han, Hui-Lin (Zootaxa, 2026)
A new species of the genus Panthea Hübner, [1820] 1816, Panthea lishana Hu, Pérez Santa-Rita & Han sp. nov. is described from Lishan National Nature Reserve, Shanxi, China. The adults, male and female genitalia, and diagnostic external characters are illustrated. Externally, P. lishana most closely resembles P. florianii Behounek, Han & Kononenko, 2013 but differs in wing pattern and genitalia traits. DNA barcoding places P. lishana in a well-supported monophyletic clade that has recently diverged from P. florianii, showing a shallow genetic divergence consistent with cryptic differentiation. An updated checklist of Panthea species is provided.